2021
DOI: 10.1002/etc.4949
|View full text |Cite
|
Sign up to set email alerts
|

Pathway‐Based Approaches for Assessing Biological Hazards of Complex Mixtures of Contaminants: A Case Study in the Maumee River

Abstract: Assessment of ecological risks of chemicals in the field usually involves complex mixtures of known and unknown compounds. We describe the use of pathway-based chemical and biological approaches to assess the risk of chemical mixtures in the Maumee River (OH, USA), which receives a variety of agricultural and urban inputs. Fathead minnows (Pimephales promelas) were deployed in cages for 4 d at a gradient of sites along the river and adjoining tributaries in 2012 and during 2 periods (April and June) in 2016, i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

5
0

Authors

Journals

citations
Cited by 16 publications
(26 citation statements)
references
References 83 publications
(154 reference statements)
0
24
1
Order By: Relevance
“…The Maumee River watershed has a history of environmental contamination related to urban (Toledo) and agricultural influences, and surface waters in the Maumee River Basin are contaminated by pesticides (Weaver et al, 1965) and pharmaceuticals (see Ankley et al, 2021; Baldwin et al, 2016). The pesticides with the most benchmark exceedances (either from the parent or a transformation product) at this site were the herbicides acetochlor, atrazine, and metolachlor, which had EAR chem or TQ chem exceedances in all 18 samples taken from the Maumee River, and the insecticide imidacloprid, which had TQ chem exceedances in all samples.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The Maumee River watershed has a history of environmental contamination related to urban (Toledo) and agricultural influences, and surface waters in the Maumee River Basin are contaminated by pesticides (Weaver et al, 1965) and pharmaceuticals (see Ankley et al, 2021; Baldwin et al, 2016). The pesticides with the most benchmark exceedances (either from the parent or a transformation product) at this site were the herbicides acetochlor, atrazine, and metolachlor, which had EAR chem or TQ chem exceedances in all 18 samples taken from the Maumee River, and the insecticide imidacloprid, which had TQ chem exceedances in all samples.…”
Section: Resultsmentioning
confidence: 99%
“…Streams in the Great Lakes Basin (USA/Canada) are of particular interest regarding pesticides due to a combination of substantial urban and agricultural inputs. Urban and agricultural streams have distinct pesticide signatures, and variability in land use can be a strong driver in the variability of occurrence and concentration of pesticides across the Basin (Ankley et al, 2021 ; Baldwin et al, 2016 ; Hladik & Kolpin, 2016 ). For example, herbicides like atrazine and metolachlor, which are used in Midwestern corn and soybean production, are frequently detected at concentrations above benchmark values in agricultural streams (Hladik et al, 2018 ; Nowell et al, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fipronil is toxic to fish and aquatic invertebrates and has been reported to elicit adverse effects at concentrations below USEPA chronic benchmarks for invertebrates (Gibbons et al, 2015; Miller et al, 2020). Atrazine is an herbicide that has a wide range of potential adverse effects to aquatic life, including reproductive dysfunction in fish and reduced growth in algal species (Richter et al, 2016; Stratton, 1984), and it has previously been identified as a chemical of concern in Great Lakes tributaries (Ankley et al, 2021; Corsi et al, 2019). As an herbicide, atrazine has the potential to impact aquatic and wetland vegetation and inhibit water‐quality improvements from wetland ecosystems (Graymore et al, 2001).…”
Section: Discussionmentioning
confidence: 99%
“…Two approaches were used to gain insight into potential adverse outcomes and biological pathways: the adverse outcome pathway (AOP) and functional annotations associated with ToxCast assay gene targets. The AOP framework has previously been used in assessment of water quality data to help interpret the significance of EAR results for estimation of potential ecological impact (Corsi et al 2019 ; Ankley et al 2021 ) and is briefly described in the present study. The ToxCast assays have been mapped to corresponding key events and molecular initiating events in AOPs defined in the AOP‐Wiki (Fay et al 2018 ; Pittman et al 2018 ; Society for the Advancement of Adverse Outcome Pathways 2018 ; Corsi et al 2019 ).…”
Section: Methodsmentioning
confidence: 99%